Public debt, iMPCs & fiscal policy transmission - Stefano Grancini (European Central Bank (ECB), 2025)
This paper investigates the relationship between public debt and the effectiveness of fiscal policy, presenting evidence of an inverse relationship between government debt and fiscal multipliers. To explain the results, I develop and calibrate a HANK model tailored to the U.S. economy. The model reveals that higher public debt diminishes fiscal multipliers by making households less constrained. Theoretically, I show intertemporal marginal propensities to consume (iMPCs) are sufficient statistics of public debt, influencing fiscal multipliers. Decomposing changes in iMPCs into components driven by wealth distribution and the policy function, I find that the primary factor driving variations in iMPCs is the change in interest rates due to the variation of government bonds. This highlights a novel mechanism: even in the absence of fiscal limits or crowding out, large stocks of debt can weaken fiscal stimulus through their effect on household behavior.
Keywords: E21; E62; E43; D31; D52; 330; Fiscal multipliers; Government bonds; Consumption heterogeneity; Interest rates; Wealth effects